Effect of purified alkaline phosphatase from Bacillus licheniformis on growth of Zea mays L. - Singh, P.; Banik, R.M. (Horizon e-Publishing Group, 2019)
Some soil microbes have the capability to solubilize mineral phosphate into organic phosphorous and used as biofertilizer to improve crop productivity in agricultural field. In this study, phosphate solubilization assay was carried out onto media plates containing calcium phsophate precipitated nutrient agar media for bacterial strains like Bacillus megaterium MTCC 453, Bacillus subtilis MTCC 1134, Bacillus licheniformis MTCC 2312, Pseudomonas aeruginosa MTCC 424, Escherichia coli MTCC 570. Among these bacterial strains, B. licheniformis MTCC 2312 showed largest clear zone of phosphate solubilzation and maximum activity of alkaline phosphatase. The enzyme alkaline phosphatase was purified from B. licheniformis MTCC 2312 with purification fold 3.52 and specific activity 295.89 U mg-1 protein using DEAE-sepharose chromatography. This enzyme showed molecular weight as 60 KD, thermostability upto 50°C, pH stability up to 8.5 and Michaelis constant (Km) and maximum activity (Vmax) as 2.30 mM and 2223 U ml-1 respectively. The lyophilized powder of this enzyme was further supplemented with media components for the growth of Zea mays for carrying tissue culture experiment. The sterilized soil supplemented with alkaline phosphatase improved the total height, dry weight, % phosphate content in the stem and root of Zea mays by 3.07, 3.15, 2.35 and 1.76 fold respectively compared to control set. This enzyme could be used at large extent as effective biofertilizer for the agricultural industry. © Singh and Banik (2019).
Keywords: Alkaline phosphatase; Bacillus licheniformis; Biofertilizer; Zea mays